What you need to know about British & American English (Learners Pub., 2004)
This booj deals with the main differences between British and American English in vocabulary and spelling, as well as important to help learners of English throughout the world understand the differences so that whichever variety they choose to speak and write, they can be confident that they are doing so correctly.